The Crucial Role Of Environmental Accounting Towards A Green Economy - Amalia, Rizky; Riesmiyantiningtias, Ninuk; Fadhilah, Amalia Tresna (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study examines how environmental accounting can help companies achieve sustainability. By analyzing various case studies, the study concludes that environmental accounting not only measures environmental impact, but also improves the efficiency and reputation of companies. Despite the challenges, engaging stakeholders is critical to the successful implementation of environmental accounting.